25-gauge histology needle versus 22-gauge cytology needle in endoscopic ultrasonography-guided sampling of pancreatic lesions and lymphadenopathy - Mavrogenis, Georgios; Weynand, Birgit; Sibille, Alain; Hassaini, Hocine; Deprez, Pierre; Gillain, Cédric; Warzée, Philippe (Endoscopy International Open, 2015)
Background and study aims: A new 25-gauge (G) endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) device (EchoTip ProCore; Cook Medical, Bloomington, Indiana, USA) has been developed, which features a hollowed-out reverse bevel to trap core samples. However, data on the differences between the diagnostic yield of the 25G EchoTip ProCore and that of a 22G standard needle are limited.Patients and methods: This pilot study included 27 patients referred during an 11-month period for EUS-FNA of pancreatic masses and enlarged lymph nodes adjacent to the upper gastrointestinal tract. Each lesion was punctured once by both a 25G EchoTip ProCore needle and a 22G standard needle (EchoTip; Cook Medical) with capillary sampling. Blinded histocytologic analyses were conducted. The final diagnosis was based on FNA findings of malignant cells, pathologic analysis of the surgical specimen, and/or radiologic and clinical follow-up of at least 7 months. Results: A total of 28 EUS-FNA procedures targeting masses of the pancreas (n = 19) and lymph nodes (n = 9) were performed. No complications were encountered. Single-pass sensitivity rates for pancreatic and lymph node malignancy were equal for the needle types: 89.5 % (95 %CI 66.82 – 98.39) and 66 % (95 %CI 24.1 – 94), respectively. There were no significant differences between the needles in terms of EUS visualization (P = 0.125), amount of blood contamination (P = 0.705), macroscopic quantity of the material (P = 0.858), quality of the cytology (P = 0.438), and adequacy and accuracy of the cell block material (P = 0.220).Conclusions: Both needles were safe and successful in terms of a high diagnostic yield, with similar histocytologic results.The results of this study were presented at Digestive Disease Week (DDW) 2014, Chicago, Illinois.This trial was registered at ClinicalTrials.gov (B027201316271).